Understanding the Impact of Uterine Fibroids on Human Endometrium Function - Navarro, Antonia; Bariani, Maria Victoria; Yang, Qiwei; Al-Hendy, Ayman (Frontiers in Cell and Developmental Biology, 2021)
Uterine fibroids (leiomyomas) are the most common benign gynecological tumors in women of reproductive age worldwide. They cause heavy menstrual bleeding, usually leading to severe anemia, pelvic pain/pressure, infertility, and other debilitating morbidities. Fibroids are believed to be monoclonal tumors arising from the myometrium, and recent studies have demonstrated that fibroids actively influence the endometrium globally. Studies suggest a direct relationship between the number of fibroids removed and fertility problems. In this review, our objective is to provide a complete overview of the origin of uterine fibroids and the molecular pathways and processes implicated in their development and growth, which can directly affect the function of healthy endometrium. One of the most common characteristics of fibroids is the excessive production of extracellular matrix (ECM) components, which contribute to the stiffness and expansion of fibroids. ECM may serve as a reservoir of profibrotic growth factors such as TGF- and a modulator of their availability and actions. Fibroids also elicit mechano-transduction changes that result in decreased uterine wall contractility and increased myometrium rigidity, which affects normal biological uterine functions such as menstrual bleeding, receptivity, and implantation. Changes in microRNAs expression in fibroids and myometrial cells, appear to modulate the TGF- pathways and the expression of regulators of ECM production. Taken together, these findings demonstrate an interaction among ECM components, TGF- family signaling, miRNAs, and the endometrial vascular system. Targeting these components will be fundamental to developing novel pharmacotherapies that not only treat uterine fibroids but also restore normal endometrial function.